2004
DOI: 10.1023/b:gres.0000026038.92932.8b
|View full text |Cite
|
Sign up to set email alerts
|

Emmer (Triticum dicoccon Schrank) in Oman

Abstract: Emmer (Triticum dicoccon) was collected recently in northern Oman. The material was analyzed morphologically and phenologically. It belongs to the Asiatic emmers (subsp. asiaticum) and not to the Ethiopian ones (subsp. abyssinicum), distributed in Ethiopia and Yemen, as originally expected. The determination of the material resulted in var. haussknechtianum and var. aeruginosum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 5 publications
3
21
0
Order By: Relevance
“…Qualitative and quantitative characters of spike parts are frequently used to evaluate and characterize wheat traits as they allow for the estimation of diversity and discrimination of closely related types (Tesemma et al 1993;Porceddu et al 1994). Results of initial surveys in the Al Hajar mountains of northern Oman and subsequent characterization of the collected wheat landraces were reported for T. aestivum L. by AlMaskri et al (2003) and for T. dicoccon Schrank by Hammer et al (2004). The reported findings of Triticum aestivum var.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Qualitative and quantitative characters of spike parts are frequently used to evaluate and characterize wheat traits as they allow for the estimation of diversity and discrimination of closely related types (Tesemma et al 1993;Porceddu et al 1994). Results of initial surveys in the Al Hajar mountains of northern Oman and subsequent characterization of the collected wheat landraces were reported for T. aestivum L. by AlMaskri et al (2003) and for T. dicoccon Schrank by Hammer et al (2004). The reported findings of Triticum aestivum var.…”
Section: Introductionmentioning
confidence: 89%
“…In Oman wheat has been cultivated since millenia. The discovery of emmer wheat Triticum dicoccon Schrank) in Oman underlines the old presence of wheat cultivation in the country (Hammer et al 2004;Al Khanjari et al 2005). Due to its location, Southwest Asia is close to the old wheat growing countries Iran, Ethiopia and Yemen of which the first two are known as major centres of wheat diversity (Vavilov 1964).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies (Al- Khanjari et al, 2007; confirmed the existence of surprisingly high levels of genetic diversity in Omani wheat landraces as already concluded from previous morphological analysis and showed that molecular markers can be used for landrace analyses and provide a means for a more detailed diversity evaluation. The high genetic diversity in the Omani durum and bread wheat landraces (Hammer et al, 2004;Gebauer et al, 2010) is most likely the result of their long history of cultivation in relatively isolated mountain oasis systems which enhanced the effects of natural and artificial selection on germplasm diversity. High diversity in traditional landraces from Oman likely reflects the effects of the germplasm old selection history and of the many agro-environments in remote mountain oases (Gebauer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Oman and the rest of the Arabian Peninsula have an ancient history of crop cultivation of indigenous as well as exotic plant species (Guarino, 1990;Hammer et al, 2004), including bread, durum, and other minor wheat species (Al-Maskri et al, 2003). However, little is known about the wealth of plant genetic resources in Oman due to a multitude of anthropogenic, physiographic and historic reasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation